Pedagogical conditions for the formation of informational and methodological competence of learners - Karlygash Sarbassova, Guldaray Akhmetzhanova,; Gulmira Tazhigulova, Gulmira Shraimanova,; Kaltayeva, Gulnar (Opción, 2019)
The article is aimed at investigating the modern views of scientists about the informational and methodological competence of students of pedagogical specializations via comparative qualitative research methods. As a result, the competency-based approach of students is changing through learning how to apply logic and methods of scientific and pedagogical research in standard situations and etc. In conclusion, full education is often seen as a necessary condition for achieving a comfortable standard of living, as an important factor in the progressive development of society and the economy